1995
DOI: 10.1038/374421a0
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclases and the interaction between calcium and cAMP signalling

Abstract: Adenylyl cyclase is the prototypical second messenger generator. Nearly all of the eight cloned adenylyl cyclases are regulated by one or other arm of the phospholipase C pathway. Functional and ultrastructural investigations have shown that adenylyl cyclases are intimately associated with sites of calcium ion entry into the cell. Oscillations in cellular cyclic AMP levels are predicted to arise because of feedback inhibition of adenylyl cyclase by Ca2+. Such findings inextricably intertwine cellular signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
404
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(425 citation statements)
references
References 60 publications
17
404
1
2
Order By: Relevance
“…Abnormalities of the cAMP-PKA signaling cascade have also been implicated in the pathophysiology of BD and as a target of lithium action (Perez et al, 2000;Chang et al, 2002). Furthermore, the cAMP system is, in turn, subject to cross-regulation by Ca 2 þ signaling through regulation at a variety of points in the cAMP signaling cascade (Choi et al, 1993;Cooper et al, 1995). Thus, it may be that multiple actions of lithium on diverse signal transduction systems are essential to its therapeutic efficacy in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of the cAMP-PKA signaling cascade have also been implicated in the pathophysiology of BD and as a target of lithium action (Perez et al, 2000;Chang et al, 2002). Furthermore, the cAMP system is, in turn, subject to cross-regulation by Ca 2 þ signaling through regulation at a variety of points in the cAMP signaling cascade (Choi et al, 1993;Cooper et al, 1995). Thus, it may be that multiple actions of lithium on diverse signal transduction systems are essential to its therapeutic efficacy in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in cells expressing ACI, which is activated by calcium͞calmodulin, alterations in cellular calcium concentrations increase cAMP accumulation (ref. 34; also for review, see 35). Since ACV and ACVI are two of the most prominent forms of AC expressed in the heart (6-9) and because oscillations in cAMP concentration in the heart have been reported to occur during cardiac contractions (36), it is tempting to speculate that the inhibition of ACV and ACVI by Ca 2ϩ may serve as a negative feedback to inhibit enzyme activity and reduce cAMP levels during a contraction.…”
Section: Resultsmentioning
confidence: 99%
“…It is blocked in the presence of the ␤ARK1-CT fusion protein, which selectively binds G ␤␥ -subunits in other preparations (Inglese et al, 1993(Inglese et al, , 1995Boekhoff et al, 1994;Koch et al, 1994). Previous studies have shown a G ␤␥ -subunit-mediated stimulation of the type II and type IV forms of adenylyl cyclase activity (Cooper et al, 1995). Another Drosophila D1-like receptor has been cloned and expressed in various mammalian cell lines and shown to activate adenylyl cyclase (Gotzes et al, 1994;Sugamori et al, 1995), but nothing is known about its mechanism of adenylyl cyclase activation or of its ability to couple directly or indirectly to multiple second messenger pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many cell types the type II and type IV forms of adenylyl cyclase activity can be stimulated by the ␤␥ subunits of G-proteins, in addition to G ␣s (Cooper et al, 1995). Thus, to see whether ␤␥ subunits are involved in the dopaminemediated increases in oocyte cAMP levels in oocytes expressing the DopR99B receptor, we have compared the effects of dopamine in the presence and absence of injections of a ␤ARK1-CT GST fusion protein.…”
Section: G-protein Couplingmentioning
confidence: 99%